Experience of treatment of children, suffering postoperative intraabdominal infiltrates - M. G. Melnichenko; V. V. Antonyuk (Клінічна хірургія, 2018)
Objective. Raising of the treatment efficacy for postoperative intraabdominal infiltrates (PII) in children, using the elaborated program of complex treatment.